THU0676 ANTI-RO/SS-A 52-KDA antibodies: a marker for lung fibrosis in rheumatic diseases. (15th June 2017) - Montoya, L Garcia; Sáenz-Tenorio, CN; González-Benítez, RD; Correyero-Plaza, M; Nieto, JC; Janta, I; Ovalles-Bonilla, JG; Martínez-Barrio, J; Serrano, B; Valor, L; Hernández-Flόrez, D; González, CM; et al.
Abstract : Background: Lung fibrosis (LF) is a type of interstitial disease that leads to lung scarring, respiratory failure and later on, death. There are 2 main types of LF: idiopathic and secondary; and the prognosis is very different. LF becomes relevant in connective tissue diseases (CTD) and some studies have suggested that there could be an association between anti-Ro/TRIM21 antibodies and the development of interstitial lung disease in these patients. Objectives: The aim of this study was to assess if the presence of anti-Ro52/TRIM21 antibodies is an independent risk factor for developing CTD-associated LF. We also aimed to evaluate the initial manifestations of systemic diseases and clinical characteristics linked to certain antibodies. Methods: It is a prospective, observational, longitudinal, single-center study conducted among unselected patients with CTD (rheumatoid arthritis, systemic lupus erythematosus (SLE), systemic sclerosis (SSc), polymyositis (PM), overlap CTD syndrome (OCTD), MCTD, primary Sjögren's sd (PSS), primary antiphospholipid sd, systemic vasculitis, and undifferentiated connective tissue disease). We analysed data from 1, 432 caucasian patients included in the "Systemic Autoimmune Diseases (SAD) Registry" from 1988 to 2014. They were all checked at least biannually and blood samples were taken according to clinical practice. Exclusion criteria were LF as the initial manifestation of the SAD, LF already diagnosed at the first visit and also LF secondary to drugs or a specific environment. Results: 10% of patients included in the study developed LF. The OR for LF in patients with anti-Ro52/TRIM21 antibodies was 1.757 (95% CI =1.1–2.7). The OR for LF increased with every year of age ( OR =1.03, 95% CI =1.02–1.04). Only 9 out of 146 patients with LF were positive for Anti-La/SS-B antibodies, and the OR for males was 8.6 compared to women (95% CI =1.8–39.5). Patients with SSc and PM showed a higher OR for the development of LF (6.9 95% CI =4.6–10.4 and 2.0, 95% CI=1.2–2.8 respectively) compared to those diagnosed with other CTD. The time passed from the first symptoms to the diagnosis of LF was inversely related to the age of onset (r=-.230; p=0.013). The average time was 60 months for patients with anti-Ro52/TRIM21 antibodies (29 patients) and 138 months for patients without them. Conclusions: Anti-Ro52/TRIM21 antibodies have been proved to be a risk factor for developing LF. The earlier the age of onset, the slower the progression to fibrosis. However, patients with anti-Ro52/TRIM21 antibodies tend to have a faster development, independent of the age of onset. Anti-La-SS-B antibodies seem to be a protective factor for the development of LF in both genders; but the association is stronger in women. Disclosure of Interest: None declared